Dental Implant Placement in Focal Osteoporotic Bone Marrow Defect: a Case Report and Treatment Recommendations - Gintaras Juodzbalys (eJournal of Oral Maxillofacial Research, 2022)
Background: Focal osteoporotic bone marrow defect is asymptomatic radiolucent area usually discovered incidentally during radiographic examination of the jaws. This bone condition can lead to clinical complications during dental implant placement or during osseointegration process.